Solve for k -1/5k+1=11

Math
-15k+1=11
Simplify each term.
Tap for more steps…
Move the negative in front of the fraction.
-15k+1=11
Combine k and 15.
-k5+1=11
-k5+1=11
Move all terms not containing k to the right side of the equation.
Tap for more steps…
Subtract 1 from both sides of the equation.
-k5=11-1
Subtract 1 from 11.
-k5=10
-k5=10
Multiply both sides of the equation by -5.
-5⋅(-k5)=-5⋅10
Simplify both sides of the equation.
Tap for more steps…
Simplify -5⋅(-k5).
Tap for more steps…
Cancel the common factor of 5.
Tap for more steps…
Move the leading negative in -k5 into the numerator.
-5⋅-k5=-5⋅10
Factor 5 out of -5.
5(-1)⋅-k5=-5⋅10
Cancel the common factor.
5⋅-1⋅-k5=-5⋅10
Rewrite the expression.
-1⋅(-k)=-5⋅10
-1⋅(-k)=-5⋅10
Multiply.
Tap for more steps…
Multiply -1 by -1.
1⋅k=-5⋅10
Multiply k by 1.
k=-5⋅10
k=-5⋅10
k=-5⋅10
Multiply -5 by 10.
k=-50
k=-50
Solve for k -1/5k+1=11

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top